(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Some recent observers noticed that employee productivity nearly in all kinds of organizations is diminishing on a day-to-day basis, particularly in the field of education. The researchers found a number of factors that affected the productivity of employees. One of the major factors contributing to the productivity of employees is workplace conflict. Therefore, the main goal of this study was to examine workplace conflicts and their effect on employee productivity. This research also examined a mediating role of workplace politics between workplace conflicts and employee productivity among the members of the faculty of general public universities in rural Sindh. A stratified sampling technique was used to collect the data from the concerned population by using a structured questionnaire. To achieve the goals of the study, different statistical techniques were used by using SPSS. A reliability test was used to check the data reliability. Furthermore, regression analysis was used to investigate the relationship between workplace conflicts and employee productivity. The finding of this test showed that the relationship between workplace conflicts and employee productivity is negative. For regression analysis, a macroprocess tool was used to investigate whether workplace politics mediates the relationship between workplace conflicts and employee productivity. The finding of this test showed that workplace politics significantly mediates the relationship between workplace conflicts and employee productivity.